2016
DOI: 10.1109/twc.2016.2586841
|View full text |Cite
|
Sign up to set email alerts
|

Caching Placement in Stochastic Wireless Caching Helper Networks: Channel Selection Diversity via Caching

Abstract: Abstract-Content delivery success in wireless caching helper networks depends mainly on cache-based channel selection diversity and network interference. For given channel fading and network geometry, both channel selection diversity and network interference dynamically vary according to what and how the caching helpers cache at their finite storage space. We study probabilistic content placement (or caching placement) to desirably control cache-based channel selection diversity and network interference in a s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
107
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(108 citation statements)
references
References 27 publications
1
107
0
Order By: Relevance
“…It's obvious that cache nodes should store the most popular files if each user can get access to only one cache node. However, the papers [3], [4] showed that caching files randomly with optimized caching probabilities is better than storing the most popular files at each cache node when one user can be served by multiple cache nodes. In [5], the authors took user mobility into consideration, where each user can move among the service regions of different cache nodes.…”
Section: A Related Workmentioning
confidence: 99%
“…It's obvious that cache nodes should store the most popular files if each user can get access to only one cache node. However, the papers [3], [4] showed that caching files randomly with optimized caching probabilities is better than storing the most popular files at each cache node when one user can be served by multiple cache nodes. In [5], the authors took user mobility into consideration, where each user can move among the service regions of different cache nodes.…”
Section: A Related Workmentioning
confidence: 99%
“…In this scenario, the content placement [93] is a relevant task that researchers are working on. In particular, researchers are working on Mobile Edge Computing (MEC) [94] and on what, where, when, and how to log cache contents.…”
Section: Cachingmentioning
confidence: 99%
“…As a result, some other works have considered optimal caching designs in large-scale small cell networks or HetNets [21]- [25]. In [21] and [22], the authors consider random caching at SBSs, and analyze and optimize the cache hit probability (i.e., the probability that a randomly requested file from the typical user is stored at its serving BS) [21] and successful offloading probability (i.e., the probability that the typical user is associated with the SBS tier and its downlink signal-to-interference-plus-noise ratio is larger than a threshold) [22].…”
Section: Introductionmentioning
confidence: 99%
“…In [24], the authors propose a hybrid caching design (consisting of identical caching in the MBS tier and random caching in the SBS tier) and a corresponding multicasting design in a large-scale HetNet, and analyze and optimize the successful transmission probability. In [25], the authors investigate how channel selection diversity affects the optimal random caching design. Note that, none of the above works [14]- [25] has considered SBS cooperation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation